Relation between exposure to respirable silica dust and silicosis in a tungsten mine in China. Issue 1 (January 1992) - Pang, D; Fu, S C; Yang, G C
Abstract : To estimate the quantitative relation between exposure to respirable silica dust and risk of an attack of silicosis, 1151 workers exposed to silica dust and employed from 1958 to 1987 in a tungsten mine in China were investigated. The results showed that the ratio of respirable silica dust concentration to total silica dust concentration was 0.529. Then, the total silica dust concentration in historical surveillance and monitoring data was converted to respirable silica dust concentration. The free silica content in respirable dust determined by x ray diffraction averaged 24.7%. Multiple logistic regression was used for the dichotomous dependent variables (presence or absence of silicosis). The independent variables in the multiple logistic regression with presence of silicosis as the dependent variable were age when first exposed, tuberculosis (presence or absence), and cumulative exposure to respirable silica dust. The partial regression coefficient of individual cumulative exposure was estimated as 0.079. It implied a positive association between exposure to respirable silica dust and risk of an attack of silicosis. The exposure limit for respirable silica dust was estimated as 0.24 mg/m3 under given conditions.